Ochratoxin A suppresses proliferation of Sertoli and Leydig cells in mice. (6th March 2019) - Park, Hahyun; Park, Hee Seo; Lim, Whasun; Song, Gwonhwa
Abstract: Ochratoxin A (OTA) is a mycotoxin originating from Penicillium and Aspergillus . In addition to toxic effects in various tissues and cells, including neurons, immune cells, hepatocytes, and nephrons, it also causes carcinogenesis and teratogenesis. Although the negative effects of OTA with respect to the pathogenesis of diseases and the malfunction of various organs have been studied widely, the biological signaling mechanisms in testicular cells are less well known. Therefore, we determined the hazardous effect of OTA in two types of testicular cells: TM3 (mouse Leydig cells) and TM4 (mouse Sertoli cells). Treatment with OTA led to a significant decrease in the proliferation of both cell lines, as revealed by an increased proportion of cells in the sub-G1 phase. In addition, the phosphorylation of signaling molecules belonging to the PI3K (Akt, P70S6K, and S6) and MAPK (ERK1/2 and JNK) pathways was regulated by OTA in a dose-dependent manner in TM3 and TM4 cells. Furthermore, the combination treatment of OTA and signaling inhibitors (LY294002, U0126, or SP600125) exerted synergistic antiproliferative effects in TM3 and TM4 cells. OTA also reduced the concentration of calcium ions in the cytosol and mitochondria, which disrupted the calcium homeostasis necessary for maintaining the normal physiological functions of testicular cells. In conclusion, the results of the present study demonstrate the mechanism underlying the antiproliferative effects of OTA in mouse testicular cells. Exposure to OTA may result in abnormal sperm maturation and the failure of spermatogenesis, which leads to male infertility.